2021
DOI: 10.1002/pon.5767
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of mechanisms influencing social inequality in cancer communication

Abstract: Objective To understand and describe mechanisms influencing social inequality in cancer communication between patients, companions and healthcare professionals. Methods The study was based on observations of 104 encounters and 30 semi‐structured interviews with nurses and medical doctors on three Danish oncology wards. Observations, interviews and subsequent analysis were guided by the theoretical framework of cultural health capital developed by Shim to investigate mechanisms that may generate social inequali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…They suggested that even when health professionals would try to communicate with the patients on other terms to make the conversations more successful, this had the opposite effect. The authors, therefore, argued that social inequality was increased in the communication between these patients and health professionals and argued for the need for additional support for patients who attended visits without relatives and possessed only a limited health capital (Dencker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that even when health professionals would try to communicate with the patients on other terms to make the conversations more successful, this had the opposite effect. The authors, therefore, argued that social inequality was increased in the communication between these patients and health professionals and argued for the need for additional support for patients who attended visits without relatives and possessed only a limited health capital (Dencker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Dencker et al (2021) showed that patients without relatives and with limited health capital often communicated poorer with health professionals than did other patients because they were often less actively involved in the conversations with the health professionals during consultations. They suggested that even when health professionals would try to communicate with the patients on other terms to make the conversations more successful, this had the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, results from an integrated review showed that nurse navigators increased trust not only between the nurse and the patient but also between the patient and the other health professionals, which had a considerable impact on the continuum of care and the communication process during the treatment pathway (Pautasso et al, 2018). Likewise, Dencker et al (2021) found that patients who were accompanied during cancer consultations were more likely to communicate well with the health professionals (Dencker et al, 2021). Similarly, we found that the interaction between patients and health professionals was influenced by the support nurse's presence during the consultations as she was able to act as the communication link between the patient and the health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be differences in communication between patients and healthcare professionals. 27 Previous studies 28,29 have shown that patients with low SEP did not engage actively in consultations and did not receive the same degree of information on treatment. Limited health literacy will make considerations of potential benefits and harms of treatment more difficult, and thus cause a delay to treatment.…”
Section: Discussionmentioning
confidence: 99%